2021
DOI: 10.3389/fpsyg.2021.641876
|View full text |Cite
|
Sign up to set email alerts
|

The 5Cs of Positive Youth Development, Purpose in Life, Hope, and Well-Being Among Emerging Adults in Malaysia

Abstract: A substantial body of evidence supports Lerner and colleagues’ 5Cs model of positive youth development (PYD) in the United States (U.S.). Nonetheless, it remains unclear whether the 5Cs can be used to identify positive development in the under-researched Asian contexts, such as Malaysia. Thus, this study examined the 5Cs of PYD (competence, confidence, character, connection, and caring) and their importance to purpose in life, hope, and well-being in a sample of emerging adult undergraduate university students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…We first calculated mean scores and standard deviations for PYD, SC, and HFE ( Table 1 ) and compared them with earlier findings. Previous studies from different parts of the world (e.g., Malaysia: Abdul Kadir and Mohd, 2021 ; Philippines: Buenconsejo et al, 2022 ; Spain: Gomez-Baya et al, 2022 ; United States: Tyler et al, 2020 ) that have employed the PYD-VSF or PYD-SF (PYD short form; Geldhof et al, 2013 ) reported the following range of mean scores for its subcomponents: Competence, 3.19 to 4.16; Confidence, 3.64 to 4.62; Character, 3.85 to 4.16; Caring 4.07 to 4.45; Connection, 3.67 to 4.17. Mean scores from our study were comparable, given that our participants scored 3.52 ( SD = 0.82) on Competence, 3.83 ( SD = 0.91) on Confidence, 4.20 ( SD = 0.57) on Character, 4.38 (0.61) on Caring, and 3.98 ( SD = 0.64) on Connection.…”
Section: Resultsmentioning
confidence: 99%
“…We first calculated mean scores and standard deviations for PYD, SC, and HFE ( Table 1 ) and compared them with earlier findings. Previous studies from different parts of the world (e.g., Malaysia: Abdul Kadir and Mohd, 2021 ; Philippines: Buenconsejo et al, 2022 ; Spain: Gomez-Baya et al, 2022 ; United States: Tyler et al, 2020 ) that have employed the PYD-VSF or PYD-SF (PYD short form; Geldhof et al, 2013 ) reported the following range of mean scores for its subcomponents: Competence, 3.19 to 4.16; Confidence, 3.64 to 4.62; Character, 3.85 to 4.16; Caring 4.07 to 4.45; Connection, 3.67 to 4.17. Mean scores from our study were comparable, given that our participants scored 3.52 ( SD = 0.82) on Competence, 3.83 ( SD = 0.91) on Confidence, 4.20 ( SD = 0.57) on Character, 4.38 (0.61) on Caring, and 3.98 ( SD = 0.64) on Connection.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the current study suggest meaningful differences in positive youth development (PYD) during emerging adulthood, which could reflect the developmental differences across the early and later years of undergraduate study. While some studies have investigated positive youth development outcomes among college students in Malaysia (Abdul Kadir & Mohd, 2021; Mohamad et al, 2014; Nouri et al, 2022), few studies specifically compare developmental differences between older and younger college students. It is essential to further examine the differences in developmental outcomes during emerging adulthood, particularly in college students who experience unique developmental tasks related to their academic and social life.…”
Section: Discussionmentioning
confidence: 99%
“…This five-factor measurement model was invariant across genders. In another recent study, Abdul Kadir et al (2021) investigated a Seven C’s model of PYD (Caring, Character, Confidence, Competence, Connection, Contribution, Creativity) and found significant factor validity among a sample of 400 university students in Malaysia. However, the study did not perform invariance testing.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have also shown that sense of life purpose plays an important role in contributing to young people's overall wellbeing, life satisfaction, reduced depressive symptoms, sense of confidence, connection, and positive relationship with society ( Abdul Kadir and Mohd, 2021 ; Chen and Cheng, 2020 ; Damon et al., 2003 ), which in turn could contribute to their academic performance. In relation to educational and college outcomes, two recent longitudinal studies showed that when high school students' sense of life purpose is oriented towards actualizing their career aspirations such as gaining expertise to excel in their chosen profession, they are more likely to apply for college ( Sharma et al., 2017 ) and complete their college education ( Sharma et al., 2021 ).…”
Section: High School Students’ Sense Of Life Purposementioning
confidence: 99%